Unique Pattern of Hypertension Fingerprints - S. Syamsurizal; Sudarni; Rapidah; Elsa Badriyya; Sintia Putri (Tropical Genetics, 2022)
The fingerprint pattern (dermatoglyphics) of each individual is not the same. Fingerprint patterns are often used as an identification tool in criminal cases and disease diagnosis. Fingerprint patterns for health diagnosis are usually diseases caused by genetic factors, for example hypertension. The purpose of this study was to describe the characteristics of fingertip dermatoglyphics of hypertensive patients. The research sample was 60 people consisting of 30 people with hypertension who visited the DR. M. Djamil Padang and controls 30 non-hypertension (normal) people from Biology FMIPA UNP students. Simple random sampling. The research variables are tendril patterns on the fingertips, the number of tendrils on the fingertips and the atd angle on the palms. The Chi-square test was used to analyze the tendril pattern data of hypertension patients. To compare the number of tendrils and the angle atd, a t-test was used. The results showed that the arch fingerprint pattern is a unique character in hypertensive patients.